Pengukuran Kepuasan Pengguna Website Politeknik ATI Padang Berdasarkan Persepsi Pengguna Internal - Sardani, Rizaldi; Ramadian, Demi; Mufti, Wahyu Fitrianda; Viarani M, Suci Oktri (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2021)
Website is an important part of any organization namely in the government, business, health and education sectors. In the world of higher education, website can be used to disseminate information related to campus life as well as a medium for promoting the existence of the campus to the outside world. As a higher education institution, Polytechnic ATI Padang own a website which is used to display various information about campus academic activities. In its management, the level of user satisfaction of the website of Polytechnic ATI Padang has never been measured. The Webqual 4.0 method used in this study aims to measure the satisfaction of internal website users by looking at the dimensions of Usability, Information Quality, Interaction Quality and Customer Satisfaction. Measurements performed by using a questionnaire instrument with Likert scale then calculated with the help of SPSS software. The results obtained that the independent variables, namely Usability, Information Quality, Interaction Quality have an influence on the dependent variable Customer Satisfaction of 70.1% and there are still 29.9% of other independent variables that can affect the dependent variable Customer Satisfaction. Furthermore, based on the results of the calculation of the satisfaction level with Likert scale, it was found that the variables of Usability, Information Quality, Interaction Quality and Customer Satisfaction received a satisfied interpretation, so it can be concluded that the Polytechnic ATI Padang website provides good service to its users.